Measuring linguistic diversity on the internet - Unesco; criador Paolillo, John C.,; criador Pimienta, Daniel; criador Prado, Daniel (Paris: Unesco, 2005)
Edited with an introduction by UNESCO Institute for statistics Montreal, Canada